اسلام میں محفوظ نکاح: صحت مند معاشرت کے قیام کے لیے اصول اور تدابیر: Safeguarding Marriage in Islam: Sharia Principles and Measures for Establishing a Healthy Society - Dr. Muhammad Akram Rana; Huzaifa Shabbir; Farhat Khan (International Research Journal of Arabic and Islamic Studies, 2024)
Islamic teachings emphasize the importance of marriage as a means to ensure the continuity of humanity and create a harmonious society. A key aspect of this is promoting “Safe Marriage”, which includes conducting medical examinations for prospective couples to prevent hereditary and contagious diseases. This practice helps safeguard the health and well-being of both partners and their future generations. The study uses a qualitative research methodology, including a review of Islamic text and teachings, to explore guidelines on safe marriage, the effects of such diseases on individuals and society, and the importance of preventive measures. It also highlights the significance of understanding and avoiding sexually transmitted diseases, such as HIV/AIDS and syphilis, which can have severe implications. Pre-marital tests are recommended to ensure a healthy, disease-free life, aligning with Islam’s goal of establishing a prosperous and protected society.